Fostering Effective Communication: Public Speaking Training for Sepama Teachers in Cambodia - Siti Asiyah; Bambang Harmanto; Diyah Atiek Mustikawati (International Journal of Community Service Learning, 2025)
Lack of teacher communication skills, especially in English, has an impact on the quality of teaching and the ability to participate in international academic activities. One effort that can be made to overcome these obstacles is to provide training and assistance in speaking in English. This study aims to analyze the improvement of educator skills in improving public speaking skills through public speaking training. The method used in this community service is training, with the subjects of this study consisting of 16 educators who participated in the training. This training was carried out through a structured approach that included the preparation, training, and evaluation stages. Surveys and Focus Group Discussions (FGD) were used as data collection methods, and the data was analyzed qualitatively. The results of the study indicate that this training program was successful in improving teachers' public speaking skills, improving their English language skills, and strengthening their self-confidence when communicating in front of an audience. This study concludes that public speaking training can improve public speaking skills among educators and ultimately improve educational standards. This program is expected to continue to support the progress of education in Sepama and improve communication standards in the academic environment.